2018
DOI: 10.1007/978-3-319-96815-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Italian Terraced Landscapes: The Shapes and the Trends

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Hence, reliable estimation on CO 2 emissions must be microrelief-specific, especially when considering that terraced fields constitute at least 10% of the entire cropland area globally (1.1 billion ha, Roser and Ritchie, 2019) and distribute widely in almost all the major grain producing regions. For instance, 22 million ha in Middle east and North Africa (Dixon et al, 2001), 13 million ha in China (Chapagain and Raizada, 2017), 133 million ha rice field in Asian-Pacific region that is often terraced (Papademetriou, 2000), as well as smaller areas such as vineyards in Europe and South America (Chapagain and Raizada, 2017;Varotto et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, reliable estimation on CO 2 emissions must be microrelief-specific, especially when considering that terraced fields constitute at least 10% of the entire cropland area globally (1.1 billion ha, Roser and Ritchie, 2019) and distribute widely in almost all the major grain producing regions. For instance, 22 million ha in Middle east and North Africa (Dixon et al, 2001), 13 million ha in China (Chapagain and Raizada, 2017), 133 million ha rice field in Asian-Pacific region that is often terraced (Papademetriou, 2000), as well as smaller areas such as vineyards in Europe and South America (Chapagain and Raizada, 2017;Varotto et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Many people are abandoning agriculture in marginal land, including the cultivation of terraces [24]. Several studies have suggested potential strategies to preserve or restore these landscapes, mostly focusing on economic incentives, community-based initiatives, and tourism [18,75,76] (Table 1). Some researchers instead suggest measures to facilitate the vegetation recolonization of abandoned terraces to reduce the erosion process and failure risks [53,59,77].…”
Section: Resultsmentioning
confidence: 99%
“…How to incentivize the farmers to keep maintaining their terraces, however, is a different matter. The Mediterranean area hosts many outstanding examples of terraced landscapes, though they are currently changing [18,25]. Many people are abandoning agriculture in marginal land, including the cultivation of terraces [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, terraced vineyards and orchards are identified as key descriptors of the Amalfi Coast, which was recognized as a Cultural Heritage Site in 1997 (UNESCO 1997). The protection and conservation of terraced landscapes in Italy pertain to the Superintendency for Architectural Heritage and Landscape (Ministry of Culture), such as the National Register of Historical Rural Landscapes and Traditional Practices (Ministry of Agriculture Food and Forestry Policies), and farmers are eligible for funding for their preservation (Caneva et al 2013;Agnoletti et al 2015;Varotto et al 2019). Although there are economic incentives, the unique landscape of the Amalfi Coast is currently threatened by the potential collapse of terraces once they start deteriorating after the abandonment of agricultural activities; the risk of these collapses is also amplified by the increasing incidence of heavy rainfall events (Caneva et al 2007;Caneva and Cancellieri 2007;Caneva 2010;Savo et al 2016).…”
Section: Introductionmentioning
confidence: 99%